2013
DOI: 10.4103/2278-960x.118645
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health care services utilization in tea gardens of Darjeeling, India

Abstract: Background: Since independence, the Government of India has made great eff orts to curb maternal mortality and morbidity by introducing various women-oriented developmental programs. Despite this, India is still struggling with a high maternal mortality and morbidity, which is compounded by low utilization of maternal health care services. Aim: The study is aimed to fi nd out the status of maternal health care services utilization and associated factors among recently delivered women in a block of Darjeeling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 32 publications
5
42
4
Order By: Relevance
“…[16] Other studies also reported similar finding with level of awareness, education of mother and PNC utilization. [17,[23][24][25] So, the education of mother is a positive factor for utilisation of postnatal care in our study, which is similar to study conducted in different parts of India, Nepal and Nigeria. In our study literacy of husbands was significantly related with utilization of PNC services.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[16] Other studies also reported similar finding with level of awareness, education of mother and PNC utilization. [17,[23][24][25] So, the education of mother is a positive factor for utilisation of postnatal care in our study, which is similar to study conducted in different parts of India, Nepal and Nigeria. In our study literacy of husbands was significantly related with utilization of PNC services.…”
Section: Discussionsupporting
confidence: 80%
“…[16] Bhattacherjee S. et al, in Darjeeling district, reported that the rates of utilization of postnatal care was 72.6%. [17] Singh Abhishek et al, in study of Socio-Economic Inequalities in the Use of Postnatal Care in India, reported that 44% of the mothers received any PNC check-up within 48 hours of giving birth, 45% of the new-borns were checked within 24 hours and around 62% of the babies did, however, eventually receive two or more check-ups within the first 10 days after birth. [18] World Health Organisation has reported that, the first 24 to 48 hours are the most critical time for postpartum woman.…”
Section: Discussionmentioning
confidence: 99%
“…23 Other studies also reported similar finding with level of education of mother and PNC utilization. [24][25][26][27] So, the education of mother is a positive factor for utilization of postnatal care in our study, which is similar to study conducted in different parts of India, Nepal and Nigeria. Utilization of antenatal and delivery care services has positive impact on the use of PNC which is similar to different studies.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, study by Bhattacherjee S et al observed that mothers with lower birth order had better odds of utilizing antenatal care services as compared to their counterparts. 20 Study by Sharma V et al also observed a statistically significant association between utilization of ANC services and parity. 21 Women of parity one or two were found to be the maximum utilizers of antenatal care services.…”
Section: Discussionmentioning
confidence: 88%